A topology optimization design of three-dimensional cooling plate for the thermal homogeneity of lithium-ion batteries. (May 2022) - Liu, Zehui; Zeng, Xin; Zhao, Weikang; Gao, Yinghui; Sun, Yaohong; Yan, Ping
Highlights: A novel topology optimization method is proposed to design the cooling plate for the battery with uneven heat generation. The temperature difference decreases up to 40% under 40C discharge. The weight is up to 80% lighter with the same temperature difference compared with traditional design under 40C discharge. Abstract: The fast charge and discharge performance of lithium-ion batteries (LIBs) is highly raised, which causes the temperature difference sharply increases. LIBs will be affected by improper thermal conditions, therefore, this work uses a novel iterative topology optimization method combined with finite element simulation to design a novel cooling plate for thermal homogeneity. The temperature difference of the battery is 14.4 °C under 40C discharge, and it decreases to 8.6 °C by using the cooling design. The temperature difference decreases up to 40%. The weight can be up to 80% lighter under the same temperature difference compared with the traditional cooling design. The novel method can be applied to different scenarios, which can decrease the temperature difference effectively and guide the structure design under complex heat sources with uneven heat generation.